Underground coal mining: Brief overview of some related problems, solutions - Eremin, Mikhail O.; Pazhin, Albert A.; Chirkov, Artyom O.; Peryshkin, Aleksey Yu; Zimina, Valentina A.; Akhmetov, Ayan Zh (AIP Conference Proceedings)
Pillars instability in underground mining of mineral resources remains one of the most acute problem of geomechanics and mining science. Rock bursts and gas bursts are known to be the major accidents at the mine sites resulting in worsening of economic efficiency of mining enterprises and lethal cases. To increase the economic efficiency and ensure the geodynamic safety of mining operations an increase of scientific background is vital. A number of issues directly related to the assessment of the sustainability of pillars are briefly discussed in the presented review. These issues are: reduction of the overburden stiffness over the mined-out space, large hanging roof spans producing an amplified abutment pressure, stress recovery, problems of limit design application, application of numerical modeling, probabilistic modeling, etc. Methods of discharging wells and directed hydraulic fracturing are discussed as major instruments for abutment pressure reduction and degassing of coal seams.